2022
DOI: 10.1111/tbed.14467
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of cellular and humoral immune responses following duck Tembusu virus infection in ducks

Abstract: Duck Tembusu virus (DTMUV), an emerging avian pathogenic flavivirus, causes severe neurological disorders and acute egg drop syndrome in ducks. However, the effects of DTMUV on duck immunological components and functions remain largely unknown. In this study, the dynamics of cellular and humoral immune responses of DTMUV-infected ducks were investigated. The numbers of CD4 + and CD8 + T, B and non-T and B lymphocytes as well as the levels of neutralizing antibodies were quantified in parallel with DTMUV loads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This difference may be attributed to the distinct viral replication capacity of each cluster in ducks. It should be noted that although the severity of disease gradually declined over the course of cluster 1 DTMUV infection, no obvious correlation was observed between neutralizing antibody titers and viral loads in blood and tissues, which contrasted with those observed in cluster 2.1 DTMUV [10,29]. This suggested that other immunological mechanisms, particularly cellular immune response, may be involved in the control of cluster 1 DTMUV infection in ducks, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 85%
“…This difference may be attributed to the distinct viral replication capacity of each cluster in ducks. It should be noted that although the severity of disease gradually declined over the course of cluster 1 DTMUV infection, no obvious correlation was observed between neutralizing antibody titers and viral loads in blood and tissues, which contrasted with those observed in cluster 2.1 DTMUV [10,29]. This suggested that other immunological mechanisms, particularly cellular immune response, may be involved in the control of cluster 1 DTMUV infection in ducks, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 85%
“…In ducks infected with DTMUV, there was a significant negative correlation between the levels of CD4+ and CD8+ T, B, and non-T and -B lymphocytes and the viral load in the blood and target organs (spleen). Additionally, significant neutralizing antibody responses were observed [126]. DTMUV infection upregulates suppressor of cytokine signaling 1 (SOCS1), leading to ubiquitination and proteasomal degradation of IRF7, ultimately inhibiting the production of type I IFNs and promoting viral replication [127].…”
Section: Innate Immune Responsesmentioning
confidence: 99%
“…Using duck models of TMUV infection, the TMUV-induced cellular immune response is beginning to be understood. TMUV induces significant up-regulation of IL-2 and IFN-γ at 7 days post infection (pi) ( 9 , 28 ), and significant increases in numbers of CD4 + and CD8 + T cells at 5 days pi ( 29 ). The E, prM/E, and C proteins were shown to induce cellular immune response by measurement of the expression of cytokines (e.g., IL-2, IL-4, IL-6, IFN-γ, and TNF-α) or the change of CD4 + and CD8 + T cell numbers in ducks following immunization with subunit vaccine, DNA vaccine, and live vector vaccine ( 13 , 14 , 17 , 19 , 20 , 22 , 27 ).…”
Section: Introductionmentioning
confidence: 99%